Financial Added Value To Increase Profitability: Processed Fish Waste Into Fish Feed Pellet Product In MSMEs “Kemuning Mandiri” - Purwanto, Setiyo; Wuryandari, Nur Endah Retno (Teumulong: Journal of Community Service, 2025)
Community service activities carried out by Dian Nusantara University (UNDIRA) lecturers to help develop business opportunities in the catfish processing industry are carried out by some home industry communities who call themselves the "Kemuning Mandiri" small business group on Jl. Rias Permai 3 No.19, Cogreg Village, Kec. Parung, Bogor Regency, West Java, has produced fish nuggets and skin crackers. This industrial activity certainly leaves behind waste in the form of bones and fish heads. The waste produced ranges from 55% – 60% of production raw materials or around 825 kg – 900 kg/month and is simply thrown away. This waste will have a negative impact on the environment if it is not handled properly and correctly. This research aims to utilize catfish bone and head waste into fish food pellet products with added financial value to increase business profits. Based on business calculations, the added financial value to increase net profits is 30.7%, or IDR 1,762,500/month.